Aprendendo a redesenhar a convivência conjulgal a partir da expectativa do transplante hepático - Medeiros, Célia Regina (2007)
This research is an investigation about feelings and adjustment of couples in their expectation of a change life with a liver transplant. For this study were conducted interviews with six couples in the age bracket between 24 to 77 years, with minimum time four years of coexistence, and expects the list of transplant from six months; diagnosis multifactorial decoupled from chemical dependency. It held an interview more or less conducted, individually containing socio-demographic issues that meet the objectives of the research. Were analyzed the contents of the verbal and non-verbal speech of the spouses, analysing for the answers related themes based on the Thematic Review. The study suggests that couples live tension and anxiety while awaiting a transplant, the entry list in the vast majority caused a catastrophic impact, the needs were presented the achievement of rapid and transplantation financial difficulties as a result of spending on disease and low pay . Attitudes of patience, understanding and more the feelings of trust, love and religious faith have been identified as resources to address the situation. The conjugal relationship after entry in the list has brought changes for couples open to the experience of covering the changing family and social group. The projects submitted and expectations have been trapped in hopes of the transplant. The conclusion which was reached in that study is: the interaction conjugal, the process of sicken has peculiarities with nuances that individual and marriage to his resignification conjugal, they needs a careful interdisciplinary quality of life to enable the couple. It is hoped that this work, help in improving the psychological support to the couple before the expectation of liver transplantation and offers clinical-theoretical allowance for professionals interested in the area of mental health